Aplikasi Berbasis Web Untuk Pendeteksian Jenis Bunga Menggunakan Algoritma K-NN - Solehatin Solehatin (Fakultas Informatika, 2018)
Flowers are part of plants that have a variety of types and forms. Because of the many varieties of flowers it is sometimes difficult to know the name of a flower that we know. It takes a data that can provide clear information about the name of the interest to be searched for the name of the interest. So needed an application that can provide information from the name of flowers through the detection of interest from a flower picture. Flower type detection can be done by knowing countour and color of flowers and using K-NN method for the classification of types of flowers. So in this study made a web-based application for the detection of interest types because later can help the detection of types of flowers quickly and easily online. This application will provide information related to the interest in the search related to the name of the interest. From the results of research conducted to identify the classification of 74.89%.